Modular Approaches to Synthesize Activity- and Affinity-Based Chemical Probes - van der Zouwen, Antonie J.; Witte, Martin D. (Frontiers in Chemistry, 2021)
Combinatorial and modular syntheses of small molecules have proven to be powerful methods in the development of new drug-like molecules. Over the past decade, these methodologies have been adapted towards utilization in the development of activity- and affinity-based chemical probes, as well as in chemoproteomic profiling. In this review, we will discuss how methods like multicomponent reactions, DNA-encoded libraries, phage displays and others provide new ways to rapidly screen novel chemical probes against proteins of interest.